A study on the use of portfolios in improving listening skill of second-year students at Hanoi University of Industry = Nghiên cứu về việc sử dụng hồ sơ bài tập trong việc cải thiện kỹ năng nghe hiểu của sinh viên năm thứ 2 tại trường ĐH Công Nghiệp Hà Nộ - Nguyễn, Thùy Trang (University of Languages and International Studies, 2017)
This study was conducted to explore the efficiency of the applicationof portfolios in the listening skill of second-yearnon English majorstudents at Hanoi University of Industries, HAUI. It took into consideration the listening progress of target students in order to generalize this method at the university. The participants included 52 second-year non English major students at HAUI. A designed listening portfolio given to students and collected at the end of the process, questionnairesand task performance measurement were employed to investigate the efficiency of listening portfolios and then, find out some suggestions on teaching and learning listening skill. Qualitative methodwasused to analyze data obtained from the aforementioned data collection instruments. This is a piece of action research and the findings of the research provided insight into the efficiency of portfolios in improving listening skill. The mid-term test results also showed that progresses were made after the process of portfolios.Based on the findings, some recommendations, limitations and suggestions were given out.